1999
DOI: 10.1046/j.1365-2648.1999.01215.x
|View full text |Cite
|
Sign up to set email alerts
|

Respite care for frail older people and their family carers: concept analysis and user focus group findings of a pan‐European nursing research project

Abstract: This paper provides a concept analysis of respite care for frail older people and their family carers. The authors re-examine the broader conceptualization of respite care delineated by Nolan & Grant, namely, users' needs for information, education and support about respite care, based on a review of recent literature and on a user focus group study. This work was undertaken by the Sheffield arm of the ACTION Project research team. ACTION is a 36-month project (1997-1999), involving Northern Ireland, The Repub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 38 publications
1
53
0
1
Order By: Relevance
“…Similarly, while the carers in this study did not command good health and had responsibility for relatives with many co-morbidities which required a great deal of physical and emotional support, their main concern was in maintaining their relative's safety and well-being when accessing any form of respite care (Ageing & Disability Department, NSW Health 1999). To achieve positive outcomes, it is critical that respite services are well equipped with more skilled and trained staff (field workers) who can deliver the quality of care while the care recipients are in respite care (Cox 1997;Hanson, Tetley & Clarke 1999). This requires service providers to offer better training for their staff to cope with complex care needs of clients, in particular when providing in home respite as indicated by the study participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, while the carers in this study did not command good health and had responsibility for relatives with many co-morbidities which required a great deal of physical and emotional support, their main concern was in maintaining their relative's safety and well-being when accessing any form of respite care (Ageing & Disability Department, NSW Health 1999). To achieve positive outcomes, it is critical that respite services are well equipped with more skilled and trained staff (field workers) who can deliver the quality of care while the care recipients are in respite care (Cox 1997;Hanson, Tetley & Clarke 1999). This requires service providers to offer better training for their staff to cope with complex care needs of clients, in particular when providing in home respite as indicated by the study participants.…”
Section: Discussionmentioning
confidence: 99%
“…A nationwide survey and consultation with various stakeholders of respite care including carers, care-recipients, respite service providers, and government bodies revealed the need for increased flexibility and availability of community based respite to accommodate individualised needs (Rhys Hearn et al 1996). In view of these findings the Commonwealth allocated almost $73 There is abundant literature on the subject of respite care for families at a state and national level (Brodaty & Gresham 1992;Hanson, Tetley & Clarke 1999;Ashworth & Baker 2000;Chappel, Reid & Dow 2001;Cox 1997;Smyer & Chang 1999), particularly for those caring for a person with a dementing or other neurodegenerative illness (Murphy 1999). Research has identified informal carers' needs and respite service availability and that service utilisation is neither uniform (Leong, Madjar & Fiveash 2001), nor meeting the demands of all groups (Braithwaite 1998;Zarit, Gaugler & Jarrott 1999).…”
Section: Supporting Literaturementioning
confidence: 99%
“…Different theories are defined in publications: they do not meet caregivers' expectations or requirements (63), families are convinced that they provide more stress than relief (64-66), they produce a sense of guilt towards patients (64).…”
Section: Balneotherapy: a New Respite Organization For Both Alzheimermentioning
confidence: 99%
“…172,179,185 Carers in these studies expressed a need for adequate financial support and information about what allowances they were entitled to, as many did not received allowances through poor knowledge. However, there was also a reluctance to divulge financial information, which acted as a barrier to seeking services.…”
Section: Costmentioning
confidence: 99%
“…14 Respite care can be provided in a number of different ways. These include care as an inpatient of a care home or hospice, typically for 1 or 2 weeks, or adult day care (ADC) or in-home or sitting services.…”
Section: Definition Of Respite Carementioning
confidence: 99%